IMPLEMENTASI KEBIJAKAN PENGADAAN TANAH DALAM PEMBANGUNAN PERLUASAN LOKASI BANDARA KOL. RA. BESSING MALINAU - Yusak Ipui; Cathas Teguh Prakoso (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
This study aims to determine the implementation of land procurement for the construction of airport location expansion Kol. Ra Bessing Malinau in Malinau District and find out whether this compensation process has guaranteed a sense of justice for the exposed community. This research uses descriptive qualitative research method. The results show that the implementation of land procurement policy is smooth, land holders are willing to follow the existing procedures. Keywords: Implementation, Land Acquisition Policy, Development